2018
DOI: 10.1063/1.5024683
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry study of Cu2ZnSnS4 bulk poly-crystals

Abstract: The linear optical properties of Cu2ZnSnS4 bulk poly-crystals have been investigated using spectroscopic ellipsometry in the range 1.2-4.6 eV at room temperature. The characteristic features identified in the optical spectra are explained by using the Adachi analytical model for the interband transitions at the corresponding critical points in the Brillouin zone (BZ). The experimental data have been modeled over the entire spectral range taking into account the lowest E0 transition near the fundamental absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In many of these works slight variations in the band gap value have been observed depending on the deviations from stoichiometry: in Cu 2 ZnSnS 4 and Cu 2 ZnSnSe 4 compounds in thin film form, an increase in the band gap with the Cu/(Zn+Sn) ratio was observed [155], including the intermediate Cu 2 ZnSn(S, Se) 4 compounds [163], probably due to a decrease in the MVB level because of a lower degree of hybridization between the Cu-d and (S, Se)-p states, consistent with the theoretical predictions. However, the opposite effect was pointed out by Levcenko et al [100] in Cu 2 ZnSnS 4 polycrystals. The same authors [159] observed a decrease in the E g value (and E 1A and E 1B ones) when the Ge/Zn ratio is increased in Cu 2 ZnGeS 4 , because of a lowering of the MCB, which is also consistent with the band structure calculations.…”
Section: Se and Band Structure Calculations In Kesteritesmentioning
confidence: 82%
See 3 more Smart Citations
“…In many of these works slight variations in the band gap value have been observed depending on the deviations from stoichiometry: in Cu 2 ZnSnS 4 and Cu 2 ZnSnSe 4 compounds in thin film form, an increase in the band gap with the Cu/(Zn+Sn) ratio was observed [155], including the intermediate Cu 2 ZnSn(S, Se) 4 compounds [163], probably due to a decrease in the MVB level because of a lower degree of hybridization between the Cu-d and (S, Se)-p states, consistent with the theoretical predictions. However, the opposite effect was pointed out by Levcenko et al [100] in Cu 2 ZnSnS 4 polycrystals. The same authors [159] observed a decrease in the E g value (and E 1A and E 1B ones) when the Ge/Zn ratio is increased in Cu 2 ZnGeS 4 , because of a lowering of the MCB, which is also consistent with the band structure calculations.…”
Section: Se and Band Structure Calculations In Kesteritesmentioning
confidence: 82%
“…Recently, Raman spectroscopy has become a widely used technique for the confirmation of quaternary phase formation, as in the case of its application in solar cell devices [84][85][86][87][88][89][90][91][92], as well as for further fundamental material analysis [93][94][95][96][97][98][99][100]. The increased popularity of Raman spectroscopy for the assessment of kesterite-type quaternary compounds, as well as of other inorganic materials, is mostly due to the strong increase in the usability and versatility of Raman systems and low qualification requirements for the general spectra analysis.…”
Section: Assessment Of Kesterite Properties and Solar Cell Performancmentioning
confidence: 99%
See 2 more Smart Citations
“…. 1.67 eV (CZTS) [3], their solid solution Cu 2 ZnSn(S x Se 1−x ) 4 (CZTSSe) includes the optimal band gap region of about 1.34 eV for single junction solar cell devices according to the Shockley-Queisser limit [4]. Ultimately, actual devices based on CZTSSe already demonstrated power conversion efficiencies of about 13% [5].…”
Section: Introductionmentioning
confidence: 99%